Response of the emergency department of a tertiary hospital during the start of the COVID-19 pandemic in Peru - Taype, Waldo (2020)
New coronavirus disease was detected in Peru in March 2020, spreading rapidly, producing serious respiratory conditions and high mortality. In the emergency service, isolation measures must be implemented for patients with specific environments for suspected and confirmed cases (depending on severity). Define care flow charts based on objective and easily evaluable data. Guidelines should be established for conducting ancillary examinations and adopting treatment based on the best available evidence. Hygiene measures and personal protective equipment must be ensured to avoid contagion, as well as suspending visits and accompaniment of family members; but at the same time, an adequate flow of information (preferably virtual) must be ensured for family members and the staff themselves. Rapid adaptation of plans and resources (material and human) is necessary to respond to the growing demand for patients; Interdisciplinary participation is essential.